Histopatologi Hepar Mencit (Mus musculus) Jantan yang Diberi Air Rebusan Plastik terhadap Antioksidan Alami - Safitri, Nuridha Audinia; Atang, Atang; Wibowo, Eko Setio (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
Plastic in Indonesian daily life cannot be avoided anymore. Materials for the manufacture of plastic can cause free radicals to the body, thus affecting the immune system. These materials are including phthalates and bisphenol-A (BPA), which commonly called as plasticizers. Free radicals in the body can be inhibited with antioxidants. Antioxidants can be obtained from endogenous (inside the body) and exogenous (outside the body). The purpose of this study was to determine the damage level of liver histopathological structure as the result of plastic boiled water induction towards natural antioxidants feeding on male mice (Mus musculus). This study used an experimental method with a completely randomized design (CRD) consisting of six treatments and five replications for 21 days. The treatments included two control groups and four other groups treated with plastic boiled water and natural antioxidants. The independent variable is natural antioxidants and the dependent variable is the liver histopathology of male mice. The qualitative parameters observed were the liver histopathological structure of male mice is in the state of inflammatory cell infiltration, degeneration, and necrosis. The research data is an overview of the liver histopathological structure of male mice. The obtained data were analyzed using descriptive qualitative analysis method. Oral induction of boiled-plastic water can affect the changes of liver histological structure. Natural antioxidants given in male mice can maintain the tissue structure as the result of boiled-plastic water induction. The results showed the damage level of male mice liver histopathological structure as reversible degeneration.